Urban poverty among Indians in Malaysia: a naturalistic inquiry - Dass, Mahaganapathy; Gill, Sarjit Singh; Redzuan, Ma'rof; Ahmad, Nobaya (Marsland Press, 2014)
This paper presents the potential significant factors of urban poverty among the minority Indian community in Malaysia through community development practice. Preliminary study was conducted at Lembah Pantai which is a well known urban squatters destination in Kuala Lumpur, Malaysia. In-depth interview which was used as the qualitative data collection method helped the researchers to holistically understand the community status, issues which can influence urban poverty. Apart from that community development domains such as participation, empowerment and capacity building are also highlighted in the study. This study reveals that the community is still facing many problems. They also argue that the developmental programs by the government are carried out by not empowering the community. However, the community feels that their problems can be solved if the community can be free of alcoholism and gangterism. It is hoped that the findings of this study will contribute to existing literature in urban poverty ground that could be an addition to the social capital theory current standing.